2022
DOI: 10.1007/s43440-022-00402-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine supplementation in patients with mild-to-moderate COVID-19 disease: a pilot study

Abstract: Background The present single-center clinical trial was designed to evaluate the potential benefits of L-carnitine supplementation in patients with COVID-19 disease. Methods and patients The study was conducted on 75 patients with mild-to-moderate COVID-19 hospitalized in Shahid Beheshti Hospital-Hamadan, IRAN. The participants were randomly divided into intervention ( n = 32) and control groups ( n = 43). The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In contrast to our findings, Talebi et al 12 reported that administration of oral LC at a dose of 3 grams daily for five days in mild to moderate COVID-19 patients reduced the CRP level in the intervention group significantly. According to a recent meta-analysis on the anti-inflammatory effects of LC, there was no relationship between dose, duration of treatment, or the reduction of CRP levels.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Talebi et al 12 reported that administration of oral LC at a dose of 3 grams daily for five days in mild to moderate COVID-19 patients reduced the CRP level in the intervention group significantly. According to a recent meta-analysis on the anti-inflammatory effects of LC, there was no relationship between dose, duration of treatment, or the reduction of CRP levels.…”
Section: Discussioncontrasting
confidence: 99%
“…It appears that LC downregulates the production of pro-inflammatory cytokines, including TNF-α, IL-6, and IL-1, thereby protecting body organs against cytokine storms. Also, a pilot study by Talebi et al 12 showed that LC administration significantly decreased erythrocyte sedimentation rate, lactate dehydrogenase (LDH), CRP, alkaline phosphatase (ALP), and creatine phosphokinase (CPK) in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Talebi et al ( 22 ) showed recently that L-carnitine supplementation promoted improvements in several parameters, including O2 saturation, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), alkaline phosphatase (ALP) activity, lactate dehydrogenase (LDH), and serum creatine phosphokinase (CPK) when compared to the intervention group. Additionally, the authors found no mortality in the L-carnitine group, while 14% of the patients in the control group died.…”
Section: Discussionmentioning
confidence: 99%
“…(Talebi et al, 2022) [132] Randomized controlled trials Patients afflicted fatty liver exhibit a decrease in AST, ALT and TG levels.…”
Section: Double-blinded Randomized Trialmentioning
confidence: 99%